Nanobodies and Nanobody-Based Human Heavy Chain Antibodies As Antitumor Therapeutics - Bannas, Peter; Hambach, Julia; Koch-Nolte, Friedrich (Frontiers in Immunology, 2017)
Monoclonal antibodies have revolutionized cancer therapy. However, delivery to tumor cells in vivo is hampered by the large size (150 kDa) of conventional antibodies. The minimal target recognition module of a conventional antibody is composed of two non-covalently associated variable domains (VH and VL). The proper orientation of these domains is mediated by their hydrophobic interface and is stabilized by their linkage to disulfide-linked constant domains (CH1 and CL). VH and VL domains can be fused via a genetic linker into a single chain variable fragment (scFv). scFv modules in turn can be fused to one another, e.g. to generate a bispecific T cell engager (BiTE), or they can be fused in various orientations to antibody hinge and Fc domains to generate bi- and multispecific antibodies. However, the inherent hydrophobic interaction of VH and VL domains limits the stability and solubility of engineered antibodies, often causing aggregation and/or mispairing of V-domains. Nanobodies (15 kDa) and nanobody-based human heavy chain antibodies (75 kDa) can overcome these limitations. Camelids naturally produce antibodies composed only of heavy chains in which the target recognition module is composed of a single variable domain (VHH or nanobody). Advantageous features of nanobodies include their small size, high solubility, high stability, and excellent tissue penetration in vivo. Nanobodies can readily be linked genetically to Fc-domains, other nanobodies, peptide tags, or toxins and can be conjugated chemically at a specific site to drugs, radionuclides, photosensitizers, and nanoparticles. These properties make them particularly suited for specific and efficient targeting of tumors in vivo. Chimeric nanobody-heavy chain antibodies combine advantageous features of nanobodies and human Fc domains in about half the size of a conventional antibody. In this review, we discuss recent developments and perspectives for applications of nanobodies and nanobody-based human heavy chain antibodies as anti-tumor therapeutics.